Difficulties of Javanese Ethnic Students Pronouncing Mandarin Vocabulary in The Department of Chinese Language and Culture at Universitas Sebelas Maret, Surakarta - Nurhusna, Nadia; Rahmanita, Raisya; Sakinah, Zaskia (Journal of Maobi, 2024)
The diversity of society in Indonesia produces differences, especially in dialects.  Dialect is a variety of languages that arises due to cultural background and the region where dialect speakers live. The Javanese dialect is famous because it has distinctive differences in intonation, language strata, and also varied accents. The pronunciation of the Javanese dialect emphasizes certain letters or what is usually called medok.  In this study, the author discusses the difficulties of ethnic Javanese students in the Department of Chinese Language and Culture at Universitas Sebelas Maret in pronouncing Mandarin vocabulary. This research uses a qualitative approach with observation methods and related literature studies. This research aims to provide an overview of the difficulties faced by Javanese ethnic students in pronouncing Mandarin vocabulary. This study found that the Javanese dialect can influence the pronunciation of Mandarin vocabulary spoken by Javanese students. By conducting this research, the author hopes that this research can provide a new perspective for readers, especially Javanese ethnic students studying Mandarin.